Mechanically Induced Multicolor Change of Luminescent Materials. Issue 9 (12th May 2015) - Ma, Zhiyong; Wang, Zhijian; Teng, Mingjun; Xu, Zejun; Jia, Xinru
Abstract Mechanofluorochromic or piezochromic fluorescence chemistry involves the switching and tuning of the luminescent properties of solid‐state materials induced by exogenous forces, such as grinding, shearing, compression, tension, and so forth. Up until now, most reported mechanochromic systems, including liquid crystals, organic molecules, organometallic compounds, polymers, and dye‐doped polymers, have displayed reversible two‐color changes, which arise from either supramolecular or chemical structure transformations. However, fluorescent materials that undergo mechanically induced multicolor changes remain rare; this Minireview is focused on such materials. Topics are categorized according to the different applied forces that are required to induce the multicolor change, including mechanical control of either the supramolecular structures or the chemical structures, and mechanical control of both the supramolecular structures and chemical structures.